"Iridium effect" in cyclometalated iridium complexes for p-type dye sensitized solar cells. (December 2019) - Légalité, Florent; Escudero, Daniel; Pellegrin, Yann; Blart, Errol; Jacquemin, Denis; Fabrice, Odobel
Abstract: Cyclometallated iridium complexes have shown great promises as photosensitizers for p-type dye sensitized solar cells (p-DSSC), in particular due to the occurrence of very long-lived interfacial charge separated states, leading to high open circuit potentials (Voc). To rationalize this experimental fact, we prepared a new series of iridium photosensitizers specially designed for NiO based p-DSSC, in order to assess the role of a panel of factors on the overall photovoltaic performances. We probed the electronic coupling between the iridium complex and the semi-conductor at the level of the anchor, the importance of the frontier orbitals distribution over the photosensitizers structures and the impact of iridium(III) vs. a lighter metal ion like ruthenium(II). The synthesis and full characterizations of these new photosensitizers are presented, and their performances within p-type DSSC are given and discussed in light of their structures. A combination of a high spin-orbit coupling and a smart design of the anchoring ligands explains the interesting performances of iridium complexes as photosensitizers for p-DSSC. Graphical abstract: Image 1 Highlights: Ir complexes as photosensitizers for NiO lead to p-DSSC with unusually high Voc. Larger interfacial charge separated state lifetime is responsible for the higher Voc. Heavy atom effect of Ir promotes the formation of a long-lived triplet charge separated state.